Dynamical implications of seasonal and spatial variations in Titan's stratospheric composition. - Teanby, N; Irwin, P; de Kok, R; Nixon, C (2009)
Titan's diverse inventory of photochemically produced gases can be used as tracers to probe atmospheric circulation. Since the arrival of the Cassini-Huygens mission in July 2004 it has been possible to map the seasonal and spatial variations of these compounds in great detail. Here, we use 3.5 years of data measured by the Cassini Composite InfraRed Spectrometer instrument to determine spatial and seasonal composition trends, thus providing clues to underlying atmospheric motions. Titan's North Pole (currently in winter) displays enrichment of trace species, implying subsidence is occurring there. This is consistent with the descending branch of a single south-to-north stratospheric circulation cell and a polar vortex. Lack of enrichment in the south over most of the observed time period argues against the presence of any secondary circulation cell in the Southern Polar stratosphere. However, a residual cap of enriched gas was observed over the South Pole early in the mission, which has since completely dissipated. This cap was most probably due to residual build-up from southern winter. These observations provide new and important constraints for models of atmospheric photochemistry and circulation.